Photophysics, Photochemical and Substitution Reactions (IntechOpen, 2023)
This book represents a unique blend of topics covering photon-initiated reactions to substitution reactions. Additionally, several fantastic chapters on the photophysics of popular dyes and their applications make the book interesting for researchers working on photon-initiated physical and chemical processes.